An analysis on the implementation of professional learning communities in Malaysian secondary schools / Tai Mei Kin and Omar Abdull Kareem - Kin, Tai Mei; Kareem, Omar Abdull (Universiti Teknologi MARA, 2021)
The main objective of the study was to examine the implementation of Professional Learning Communities (PLCs) in Malaysian secondary schools. The study was conducted by using quantitative method whereby a total of 971 principals, senior assistants and teachers were involved in the survey. The descriptive statistical analysis was employed to obtain scores and means whereas the t-test and ANOVA were adopted to test the significance of the concerned variables. The result revealed that, i) the schools were rated as Quite Good in practicing PLCs; ii) comparing the two dimensions of PLCs, Organizational Factor achieved a higher mean score than Non-organizational Factor; iii) among all the sub-dimensions, Principals' Commitment and Support achieved the highest whereas External Support System achieved the lowest mean score. The study summarized that although contextual factors such as decentralized school system, the policy environment and teachers' workload are potential factors that might impact the development of PLCs, the incompetence of the teachers in practicing Collaborative Learning, Collective Inquiry and Reflective Dialogue would significantly hinder their professional practices in PLCs. The study offers an analysis in exploring PLCs towards sustained school improvement and may help move the current available literature to a more coherent, theoretical perspective for practical engagement.